JURIDICAL REVIEW OF THE INHERITANCE RIGHTS OF ADOPTED CHILDREN IN THE PERSPECTIVE OF THE CIVIL CODE - Citra Dewi Saputra; Mila Surahmi; Zaimah Husin; M. Martindo Merta (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This research examines the legal perspective of the inheritance rights of adopted children based on the Indonesian Civil Code. Inheritance is the transfer of property rights from a deceased person to living heirs, and in many cases, adopted children may be entitled to inherit from their adoptive parents. However, the status of adopted children in inheritance laws can be complex and raises various legal issues. The study explores the concept of adoption and its implications on the inheritance rights of adopted children. It analyzes relevant provisions of the Indonesian Civil Code and other related legal texts to understand the legal status of adopted children as heirs. The research also investigates the challenges and problems that may arise in determining the inheritance rights of adopted children, particularly when there are natural descendants or other adoptive children involved. By adopting a qualitative research approach, the study gathers data through legal document analysis and interviews with legal experts. The findings shed light on the legal intricacies surrounding the inheritance rights of adopted children and provide insights into the recognition and protection of their rights under the prevailing legal framework. The research contributes to the understanding of the legal complexities surrounding adoption and inheritance in Indonesia and highlights the importance of addressing these issues to ensure fair and just treatment of adopted children in matters of inheritance.